Xunzi on Empathy: A Confucian and Biological Naturalist Viewpoint - Tan, Boon Chuan (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2016)
It is said that a science of empathy is emerging from several disciplinary studies in the West. As a biological naturalist from ancient Confucian school, Xunzi (circa 313BCE-218BCE) shares much of his modern Western counterparts on biological understanding of empathy with three but minor differentiations, that is terminology, approach and the goal of the empathy respectively. The aim of this paper is to provide an elaboration and justification to Xunzi’s Confucian philosophy that he would like to join and expand the empathic progress with the contemporary ‘age of empathy’ or ‘empathic civilization’ proposed by his Western counterparts today.